Malasakit in a public company expressions of kapwa, buhay, ginhawa, dangal and tulong in the workplace - Reyes, Jesusa R. (Quezon City Tri-College, University of the Philippines Diliman, 2018)
This study of Malasakit as an organizational core value using various qualitative research techniques and the case study method probed into the practices and meanings of Malasakit in the three layers in the organization, in their work and social relations, within and outside the organization as well as their involvement in the corporate social responsibility (CSR) initiatives of the company. In the public utility company that was studied, Malasakit was chosen as an organizational core value to enable the company to respond to a crisis; and survive and continue its operations and services to the wider public. The meanings of Malasakit were related to Filipino characteristics of Kapwa, Buhay, Dangal and Ginhawa and came out relevant in understanding its practice in the workplace. In the course of the study, Tulong also emerged as important in understanding Malasakit. The major findings and empirical data revealed that the employees' understanding and practice of Malasakit is multi-faceted. As a common definition, the top and middle management, together with the rank and file employees understand Malasakit as performing one's work by going beyond duty or standards towards assisting the company and people around them, whether employees, customers, other stakeholders, and family members while expecting the company to do the same for them. Malasakit grounded in concern for kapwa facilitated union relations and employee volunteerism through the CSR initiatives of the company. This study will help in understanding the relevance of a Filipino Value, such as Malasakit and in relations in and outside the workplace."--Author
Thesis (Doctor of Philosophy in Philippine Studies)--University of the Philippines Diliman
Keywords: Corporate culture -- Philippines; Organizational behavior -- Philippines; Interpersonal relations -- Philippines